PRAGMATIC DIETETICS OF FORGETTING AND THE CRITICISM OF THE CARTESIAN NEUROTICISM - ZheronkіnА. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
In the article we consider the epistemological ideas of C. S. Pearce through the prism of the historical and philosophical approach of P. Hadot. We argue the view of his conception of experimentation and logical schematism as specific dietetical practice that open to a subject not a very truth, but an access to free search it. In the article we also consider the views of the initiator of modern discourse about the memory F. Nietzsche about the problem of correlation between forgetting and cognitive activity. The epistemological views of C. Pierce and F. Nietzsche are united in ambition to overcome not only the rationalistic philosophy of R. Descartes, but also the neurotic Cartesian concept of subjectivity at all.